2019
DOI: 10.1158/1541-7786.mcr-19-0245
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Protein Translation by the Integrated Stress Response Maintains the Proliferative and Migratory Capacity of Lung Adenocarcinoma Cells

Abstract: The integrated stress response (ISR) is a conserved pathway that is activated by cells that are exposed to stress. In lung adenocarcinoma, activation of the ATF4 branch of the ISR by certain oncogenic mutations has been linked to the regulation of amino acid metabolism. In the present study, we provide evidence for ATF4 activation across multiple stages and molecular subtypes of human lung adenocarcinoma. In response to extracellular amino acid limitation, lung adenocarcinoma cells with diverse genotypes commo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Part of these were also significantly upregulated at the mRNA level in our RNA-seq data (i.e. Pck2 and CHOP), while others were not (Gpx1, PUMA, Bim) (supplementalFigure 3F), possibly reflecting activation of the latter at the translational level, as described in other ISR-related contexts(53,54). Two other known effectors of the ISR, Hrk and NOXA (51), were not expressed in FL mycER cells as judged by our RNA-seq data, precluding assessment of their possible roles in IACS-010759-induced cell death.In order to assess the contribution of the ISR to the cytotoxic action of IACS-010759, we used CRISPR-Cas9 engineering to inactivate the gene encoding CHOP, the main mediator of the proapoptotic branch of the ISR(45).…”
supporting
confidence: 58%
“…Part of these were also significantly upregulated at the mRNA level in our RNA-seq data (i.e. Pck2 and CHOP), while others were not (Gpx1, PUMA, Bim) (supplementalFigure 3F), possibly reflecting activation of the latter at the translational level, as described in other ISR-related contexts(53,54). Two other known effectors of the ISR, Hrk and NOXA (51), were not expressed in FL mycER cells as judged by our RNA-seq data, precluding assessment of their possible roles in IACS-010759-induced cell death.In order to assess the contribution of the ISR to the cytotoxic action of IACS-010759, we used CRISPR-Cas9 engineering to inactivate the gene encoding CHOP, the main mediator of the proapoptotic branch of the ISR(45).…”
supporting
confidence: 58%
“…Further, pharmacological ISR activation is protective in a Huntingtin mouse model 53 . Nevertheless, deregulated activation of the ISR has also been correlated with cancer and diabetes 54,55 . The ISR is activated in neurogenerative disorders, traumatic brain injury, and Down syndrome [56][57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pathologic changes caused by viruses can induce cancerous changes in cells, such as HCC development in patients with HCV infection [163,164]. Some studies have shown that eIF2α phosphorylation inhibits c-Myc-mediated glycolysis, thereby inhibiting cancer growth and metastasis [165,166]. Therefore, the study of eIF2α has played an important role in revealing viral pathogenesis and new targeted drug development.…”
Section: Resultsmentioning
confidence: 99%